Standardization of seed testing protocols and TZ test in senna (Cassia angustifolia) - UDAYA BHASKAR K.; S.S. PARIHAR; M. DADLANI; SHIV K. YADAV (Seed Research, 2026)
Senna is a cultivated annual herb valued in medicine for its cathartic properties. Based on studies conducted on thirty samples of senna revealed that working sample size for physical purity and other crop seed determination was found to be 65 g and 650 g respectively. Seeds can be tested using rolled paper towel method at 25°C with first and final count (days) 6 and 11. Senna exhibited physical dormancy as considerable number of seeds did not imbibe water at the end of germination test and sulphuric acid treatment for 30 minutes was found to be effective for alleviation of coat-imposed dormancy. Germination studies for three years revealed normal seedlings percentage in senna varied from 10 to 65 in control and 28 to 90 in H₂SO₄ treatment for 30 minutes. Topographical tetrazolium chloride (TZ) test was also standardized for senna and finally seed standards were suggested based on our results of experimentation and perusal of standards in IMSCS (Indian Minimum Seed Certification Standards) of concerned family i.e. fabaceae.